2022
DOI: 10.1073/pnas.2111283119
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 1a-mediated dendritic wiring of the Drosophila mushroom body extrinsic neurons

Abstract: Significance The adult Drosophila mushroom body (MB) is one of the most extensively studied neural circuits. However, how its circuit organization is established during development is unclear. In this study, we provide an initial characterization of the assembly process of the extrinsic neurons (dopaminergic neurons and MB output neurons) that target the vertical MB lobes. We probe the cellular mechanisms guiding the neurite targeting of these extrinsic neurons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…γ2,α'1 MBON dendrites were seen throughout the γ lobe in the transverse plane and slightly extended along the lobe in the coronal z-projection (Figure 6G). Consistent with a recent study of MBON morphology in HU-fully ablated animals, we also observed γ2,α'1 MBON dendrites to arborize more sparsely in the lobes, with slight extension outside the lobes (Lin et al, 2022).…”
Section: Anatomic and Functional Properties Of Downstream Circuitry I...supporting
confidence: 92%
“…γ2,α'1 MBON dendrites were seen throughout the γ lobe in the transverse plane and slightly extended along the lobe in the coronal z-projection (Figure 6G). Consistent with a recent study of MBON morphology in HU-fully ablated animals, we also observed γ2,α'1 MBON dendrites to arborize more sparsely in the lobes, with slight extension outside the lobes (Lin et al, 2022).…”
Section: Anatomic and Functional Properties Of Downstream Circuitry I...supporting
confidence: 92%
“…As indicated previously, the MBONs and DANs innervating the adult vertical lobes are mostly incorporated into the MB network during metamorphosis (Truman et al, 2022). Recently, my team followed the development of these extrinsic neurons during the pupal stage and found that their axons or dendrites sequentially innervate the MB zones in a stereotyped pattern (Lin et al, 2022). In general, innervation by the DAN axons initiates from the zones near the base of the vertical lobes and finishes at the tips of the vertical lobes, whereas the MBON dendrites innervate from the opposite direction, i.e., from the tips to the base.…”
Section: Assembly Of the Mbons And Dansmentioning
confidence: 72%
“…In contrast to the dispensable role of neighboring MBONs and DANs, KC axons are necessary for the correct arborization patterns of both MBON dendrites and DAN axons. In alpha lobe absent (ala) mutant flies in which the MB vertical lobes are absent, most MBON dendrites and DAN axons that normally target the vertical lobes wander around the missing lobes (Pascual and Preat, 2001;Pascual et al, 2005;Lin et al, 2022). Strikingly, when their usual target zone in the α′ lobe is missing, the MBON-α′2 dendrites steer away to innervate the β′2 zone of the horizontal lobes (a less prominent ectopic innervation is also found in an α′-like zone).…”
Section: Assembly Of the Mbons And Dansmentioning
confidence: 99%
See 2 more Smart Citations